"Narrative Cloggers": Notes on Description and Subversion in Nicholson Baker’s Fiction - Françoise Sammarcelli (European Journal of American Studies)
This paper argues that the proliferating descriptive passages in Nicholson Baker's novels seem to short-circuit narrative progression instead of being mere additives to the narrative, in a textual exploration which blurs the traditional distinction between description and narration. The essay focuses on three of Baker’s novels and comments on the evolution in Baker’s work between 1988 and 2003, from the exuberant description of objects in The Mezzanine (1988), to a more intimate rehistoricizing of the object as a trace of the narrator’s experience as a family man in Room Temperature (1990), to the repeated encoding of daily life as an ever-renewed mystery in A Box of Matches (2003).Dwelling on the various strategies at work in Baker’s descriptions (such as his frequent experiment with conjunction and disjunction, or his particular use of metaphor and metonymy), this paper also shows how the humorous defamiliarization of the visible contributes to the resistance of the texts. From the emphasis on material objects (and the body) to that on the materiality of signifiers, this leads to a discussion of the metatextual dimension of description.